Japanese Advertisements with Systemic Functional Linguistics (SFL) and Multimodal analyzed - Sri Aju - Indrowaty; Ika Farihah Hentihu (Universitas Brawijaya, 2023)
Advertising is an endless source of research. The language used in advertising is a language that is easy to understand and persuasive. This paper discusses the Japanese language of Japan’s advertisements taken from printed and online magazines. This research was analyzed with Systemic Functional Linguistics (SFL) by Halliday and Hasan (1985: 64 ) and Multimodal by Kress & van Leeuwen (1996, 2006). This research is qualitative and descriptive and analyzed as grammar of Japanese advertisements. The objects of the advertisement were obtained in three stages of advertising - pioneering, competitive, and retentive stages. This type of pioneering advertising is used in the introductory stages of the life cycle of a product. Competition is useful when the product has reached the market-growth and especially the market-maturity stage. The Retentive advertisement is when the product has achieved a favorable status in the market, maturity, or declining stage. The results showed that many Japanese advertisements in pioneering and competitive steps can be analyzed with SFL and used material process. In the Retentive step, many ads are in ellipsis words so only analyzed with Multimodal. All the advertisements used the grammar of material and relational processes. This paper is useful not only for the linguistic world, especially Japanese linguistics but also for the actors or advertisers so that consumers are more interested in using their products